The Role of Green Economy in Climate Change Mitigation - Firnando, Hero Gefthi (International Journal of Islamic Finance, 2023)
Abstract As the world confronts the escalating challenges of climate change, the role of the green economy has come to the forefront in the quest for effective mitigation strategies. This paper, titled "The Role of Green Economy in Climate Change Mitigation," delves into the pivotal relationship between green economic practices and the mitigation of climate change impacts. The green economy, characterized by sustainable and environmentally responsible practices, presents a paradigm shift in economic development. This research investigates how the adoption of green economic principles and initiatives can significantly contribute to reducing greenhouse gas emissions, enhancing energy efficiency, and fostering a more sustainable relationship between society and the environment. Through a comprehensive review of existing literature, case studies, and policy analyses, this study examines the multifaceted dimensions of the green economy's role in climate change mitigation. It explores the impact of green technologies, renewable energy sources, sustainable transportation, and circular economy models on mitigating the adverse effects of climate change. The findings highlight the potential of the green economy as a catalyst for climate action, offering not only economic growth but also a path towards a low-carbon and climate-resilient future. The research underscores the importance of integrating green economic principles into national and international climate policies, emphasizing the need for collaborative efforts across sectors to address one of the most pressing global challenges of our time. This study serves as a valuable resource for policymakers, environmental advocates, and stakeholders interested in harnessing the transformative power of the green economy to mitigate climate change and secure a sustainable future for all.